A New Species of Hypomasticus from Eastern Brazil Based on Morphological and Molecular Data (Characiformes, Anostomidae) - Birindelli, Jose L. O.; Melo, Bruno F. [UNESP]; Ribeiro-Silva, Luis R. [UNESP]; Diniz, Debora; Oliveira, Claudio [UNESP] (Amer Soc Ichthyologists & Herpetologists, 2020)
A new species of Hypomasticus is described from the Rio de Contas, a coastal drainage of eastern Brazil, and its phylogenetic position is proposed based on molecular data. The new species is diagnosed among Anostomidae by possessing a downturned mouth with compressed teeth arranged side by side, 37 or 38 lateral-line scales, three scale series between the dorsal-fin origin and the lateral line and between the lateral line and the pelvic-fin origin, and 12 scale rows around the caudal peduncle. Mitochondrial DNA sequences provide evidence that the new species is closely related to H. mormyrops, H. thayeri, H. copelandii, and H. steindachneri, a clade of species endemic to coastal drainages of eastern Brazil. These results combined with a previous phylogeny support the reallocation of the latter two species from Leporinus to Hypomasticus. The new species is herein considered to be Endangered under the IUCN criteria, due to a small Extent of Occurrence, severely fragmented population, and continued decline of area, extent, and quality of habitat.